Pieces of the past : a stroll down Jamaica's memory lane - Tortello, Rebecca (Ian Randle Pub. KingstonJM, 2007)
Brings together interesting people and events from the nation's past to the general public. Ranges from the strictly historical such as the founding of Jamaica's two political parties, to reminiscences of service in World War II, to the exploration of place names and proverbs.